Femoral Neck Stress Fracture in Air Force Basic Trainees. Issue 1 (1st January 2014) - Kupferer, Kevin R.; Bush, David M.; Cornell, John E.; Lawrence, Valerie A.; Alexander, Jeffrey L.; Ramos, Rosemarie G.; Curtis, Denice
ABSTRACT: Stress fractures are a common overuse problem among military trainees resulting in preventable morbidity, prolonged training, and long-term disability following military service. Femoral neck stress fractures (FNSFs) account for 2% of all stress fractures but result in disproportionate burden in terms of cost and convalescence. The purpose of this study was to describe and investigate FNSF in U.S. Air Force basic trainees and to present new data on risks factors for developing FNSF. We examined 47 cases of FNSF occurring in Air Force basic trainees between 2008 and 2011 and 94 controls using a matched case–control model. Analysis with t tests and conditional logistic regression found the risk of FNSF was not associated with body mass index or abdominal circumference. Female gender ( p < 0.001) and slower run time significantly increased risk of FNSF (1.49 OR, p < 0.001; 95% CI 1.19–1.86). A greater number of push-up and sit-up repetitions significantly reduced risk of FNSF (0.55 OR, p = 0.03; 95% CI 0.32–0.93; 0.62 OR, p = 0.04; 95% CI 0.4–0.98) for females. In this study body mass index was not correlated with FNSF risk; however, physical fitness level on arrival to training and female gender were significantly associated with risk of FNSF.